The potential impact of generative AI on the future of higher education: a game-changer or a danger to academic integrity - Kumar, Pritam; Mastana, Amarjeet Singh; Rungruengarporn, Chainarong; Chantokul, Donyawan (International Journal of Evaluation and Research in Education (IJERE), 2025)
Artificial intelligence (AI) has the potential to improve education by substantially modifying knowledge acquisition. While the research on AI’s incorporation into higher education is growing, significant gaps exist in understanding its responsibilities, potential, implications for ethics, and privacy problems in educational settings. This study investigates AI’s transformative impact on higher education using a total of four essential objectives: the ever-growing capabilities of AI within customized instruction, the prospective use of smart tutoring platforms, AI-driven review and input procedures in learning evaluation, and the ethical and privacy issues inherent in these technologies. A systematic review of the literature (SLR) was carried out to answer research questions established utilizing population, intervention, comparison, outcome, and context (PICOC) criteria, resulting in a structured analysis of pertinent articles. To conduct a thorough literature search, the Publish or Perish (version 8) application and an API key were used to systematically access the Scopus database. Initial keyword searches yielded 567 articles, which were reduced to 29 following predetermined relevant screening, restricted access sorting, repetition removal, and content validation. The findings show that AI technologies are increasing personalized education by adapting instructional content to individual needs while also improving decision-making, resources deployment, and administrative duties. However, the integration of AI raises issues such as data privacy, potential redundancies of human educators, and ethical obstacles. These findings highlight AI’s immense potential for higher education, underlining the importance of tackling these problems regarding responsible and inclusive integration, furthering future research, and developing processes for responsible AI use in educational environment.